2011
DOI: 10.1007/s00468-011-0575-5
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis induction system for cloning an adult Cyphomandra betacea (Cav.) Sendt. (tamarillo)

Abstract: Somatic embryogenesis is a valuable tool for plant breeding. In recent years, different aspects related to somatic embryogenesis (SE) induction in tamarillo have been studied at our laboratory. In this work, results concerning the establishment of a protocol for cloning an adult tamarillo tree through SE are presented. Attempts to induce SE in tamarillo from various explants directly taken from an adult tree were unsuccessful and only calli with no embryogenic potential were initiated. To overcome the lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 31 publications
(41 reference statements)
6
31
0
2
Order By: Relevance
“…Our conclusions are consistent with the previously demonstrated genotoxic effect of picloram with various mutagenens tests in plants (Mohammed and Ma, 1999;Salvi et al, 2001;Correia et al, 2011). Sawamura and Jackson, (1968) have reported that picloram decreased the rate of cytoplasm streaming in stamen hairs of Tradescantia, while Brownian movement increased and numerous and size of chloroplasts affected in Vicia leaf.…”
Section: Resultssupporting
confidence: 82%
“…Our conclusions are consistent with the previously demonstrated genotoxic effect of picloram with various mutagenens tests in plants (Mohammed and Ma, 1999;Salvi et al, 2001;Correia et al, 2011). Sawamura and Jackson, (1968) have reported that picloram decreased the rate of cytoplasm streaming in stamen hairs of Tradescantia, while Brownian movement increased and numerous and size of chloroplasts affected in Vicia leaf.…”
Section: Resultssupporting
confidence: 82%
“…robur (San-José et al 2010), as well as other fruit trees (Correia et al 2011). In the present study, the approach was applied to Q. alba, in which initiation of SE was effective with explants obtained from cultures during active shoot growth.…”
Section: Discussionmentioning
confidence: 97%
“…Somatic embryogenesis induction followed the protocols of Canhoto et al (2005) and Correia et al (2011). Briefly, wounded leaves were placed abaxial side down on the induction medium (MS basal medium supplemented with 20 lM Picloram and 0.26 M sucrose, P medium).…”
Section: Somatic Embryogenesis Inductionmentioning
confidence: 99%
“…betacea can be propagated by seeds or through conventional macropropagation techniques such as grafting or cuttings (Slack 1976;. In vitro protocols have also been applied, including axillary shoot proliferation (Obando and Jordan 2001), organogenesis (Atkinson and Gardner 1993) and somatic embryogenesis (Guimarães et al 1988;Lopes et al 2000;Canhoto et al 2005;Correia et al 2011. Somatic embryogenesis has proved to be particularly interesting since high rates of somatic embryo induction and plant conversion can be achieved both from juvenile and adult selected trees .…”
Section: Introductionmentioning
confidence: 99%